2022
DOI: 10.1111/vox.13232
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of anti‐D alloimmunization in D‐negative individuals receiving D‐positive red blood cell transfusion: A systematic review and meta‐analysis

Abstract: Background and Objectives The transfusion of D‐negative red blood cells (RBCs) to D‐negative patients has been widely adopted to prevent anti‐D alloimmunization, especially in women of childbearing age. Still, transfusion of D‐positive RBCs to D‐negative recipients is occasionally inevitable in practice, and the resulting incidence of anti‐D in different D‐negative groups of patients has not been well summarized. Materials and Methods We searched the relevant literature using PubMed, Cochrane Library, and Emba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
0
10
1
Order By: Relevance
“…The upper limit of the 95% CI for alloanti-D incidence (8.40%) in the trial group was far lower than the lower limit of the 95% CI (19.0%) in the true D-control group, as previously estimated in our meta-analysis. 32 In a large nationwide retrospective study, we found no anti-D immunization in any Asian-type DEL pregnant women (n = 1,032), despite their high probability of carrying D+ fetuses (>95%) due to the low prevalence of D heterozygotes (7%) in fathers. 29,36 In line with this, no Asian-type DEL but only true D-individuals were identified in another group of pregnant women who had developed alloanti-D (0/127), which is in agreement with two previous independent studies (0/165).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The upper limit of the 95% CI for alloanti-D incidence (8.40%) in the trial group was far lower than the lower limit of the 95% CI (19.0%) in the true D-control group, as previously estimated in our meta-analysis. 32 In a large nationwide retrospective study, we found no anti-D immunization in any Asian-type DEL pregnant women (n = 1,032), despite their high probability of carrying D+ fetuses (>95%) due to the low prevalence of D heterozygotes (7%) in fathers. 29,36 In line with this, no Asian-type DEL but only true D-individuals were identified in another group of pregnant women who had developed alloanti-D (0/127), which is in agreement with two previous independent studies (0/165).…”
Section: Discussionmentioning
confidence: 71%
“…Primary alloanti-D immunization in D-recipients commonly occurs between 2 and 3 months after D+ RBC transfusion, and secondary alloanti-D immunization generally occurs within 1 month. 32 Once alloanti-D is produced, disappearance is unlikely. 40 Hence, we chose to follow the patients for more than 3 months to avoid false negative results if the anti-D immunization was delayed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The guideline recommends using Rh‐D‐negative blood for boys aged <18 years. The D‐immunisation rate is 27% in trauma patients, 21 and it is unclear if this is a cost‐effective strategy given that children have lower alloimmunisation rates 22 …”
Section: Trial Name Number Of Patients Trial Design Key Findingsmentioning
confidence: 99%
“…The D-immunisation rate is 27% in trauma patients, 21 and it is unclear if this is a cost-effective strategy given that children have lower alloimmunisation rates. 22 What ongoing trials are likely to inform our haemorrhage response?…”
mentioning
confidence: 99%